Peru : Country Program Evaluation for the World Bank Group, 2003-09 - Independent Evaluation Group (Washington, DC: World Bank, 2012)
Since 2003, Peru has emerged as an open, rapidly growing economy. Over the review period of 2003-09, successive governments adopted policy platforms aimed at maintaining macroeconomic stability, furthering the private sector supply response, broadening participation in growth, improving social service delivery, and strengthening public institutions. The World Bank Group (WBG) supported each of the three pillars of the government's poverty reduction strategy, namely: (i) broad-based economic growth that engaged a higher share of the population; (ii) enhanced human development through improved social service delivery; and (iii) strengthened public sector institutions. Independent Evaluation Group (IEG) recommends that the WBG: (i) tailor its strategy to support long-term integration of Peru's three distinct regions; (ii) seek opportunities to support large-scale infrastructure development; (iii) develop a more strategic approach to helping improve public sector management; (iv) seek further innovations in International Bank for Reconstruction and Development (IBRD's) instruments against a backdrop of declining demand for its financial resources; (v) seek to help develop a strategic planning function in Peru; (vi) build a close strategic partnership with development partners that provides concessional finance in the social sectors to optimize synergies with IBRD policy lending and analytic and advisory activities; (vii) develop a strategic focus for International Finance Corporation (IFC) around employment- generating industries in emerging sectors; (viii) maintain IFC's additionality by supporting lower-tier and more regionally dispersed private companies; and (ix) leverage the strong country presence of IBRD and IFC to enhance Multilateral Investment Guarantee Agency's (MIGA's) marketing and risk assessment functions.